Research on the fluid dynamics interaction between submarine sand waves and seawater by seismic oceanography - Han, Tonggang; Chen, Jiangxin; He, Bingshou; Azevedo, Leonardo (Frontiers in Marine Science, 2023)
Introduction The seafloor is an important interface between the lithosphere and the hydrosphere, where processes related to circulation and energy exchange happen along with various marine processes widely developed in the water column near the seafloor. These processes are still not yet completely understood as there are constraints of submarine detection technology and the interdisciplinary nature of these complex environments. Seismic reflection data have been a preferable tool to study and image these processes due to their characteristics in terms of spatial resolution. In seismic reflection data, submarine sand waves show hair-like reflection configurations with low continuity and wearing-hair style, appearing with an angle with the seafloor. Investigation of the relationship between the characteristics of submarine sand waves induced hair-like reflection configuration and hydrodynamics is crucial for understanding hair-like reflection configuration generation and spatiotemporal evolution. Methods This study combines fluid dynamics numerical simulation and seismic oceanography to discuss the seismic response characteristics and formation mechanisms of the hair-like reflection configuration. First, we create a seawater time-variant fluid-dynamical model followed by the numerical simulation of seismic oceanography data. This procedure results in seismic oceanography numerical simulation sections with hair-like reflection configurations for different constant flow conditions forced on the boundary. Optimal matching method is then applied to interpret field seismic reflection sections given the results obtained with the numerical experiments. Results and discussion As consequence, the fluid dynamic explanation for the formation mechanism of the hair-like reflection configuration due to differences in seawater thermohaline is proposed. The study provides additional comprehension and further insights into the dynamic process of submarine sand waves induced hair-like reflection configuration using the seismic oceanography method.